2010
DOI: 10.1051/0004-6361/200913455
|View full text |Cite
|
Sign up to set email alerts
|

The interface between the stellar wind and interstellar medium around R Cassiopeiae revealed by far-infrared imaging

Abstract: Aims. The circumstellar dust shells of intermediate initial-mass (∼1 to 8 M ) evolved stars are generated by copious mass loss during the asymptotic giant branch phase. The density structure of their circumstellar shell is the direct evidence of mass loss processes, from which we can investigate the nature of mass loss. Methods. We used the AKARI infrared astronomy satellite and the Spitzer space telescope to obtain the surface brightness maps of an evolved star R Cas at far-infrared wavelengths, since the tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
4
21
0
Order By: Relevance
“…If U Hya is moving through an interstellar medium stationary to the sun, the offset should be opposite to the proper motion, PA at −48 • . An additional PA offset of −37 • may suggest a flow of interstellar matter in the plane of the sky with respect to the Sun (see Ueta et al 2008Ueta et al , 2010. If so, a downstream wake should appear, not around PA = −48 • , but around PA = −85 • ± 15 • .…”
Section: Offset Of the Shell Centermentioning
confidence: 99%
“…If U Hya is moving through an interstellar medium stationary to the sun, the offset should be opposite to the proper motion, PA at −48 • . An additional PA offset of −37 • may suggest a flow of interstellar matter in the plane of the sky with respect to the Sun (see Ueta et al 2008Ueta et al , 2010. If so, a downstream wake should appear, not around PA = −48 • , but around PA = −85 • ± 15 • .…”
Section: Offset Of the Shell Centermentioning
confidence: 99%
“…Sahai and Trauger 1998). Ueta et al (2009) reported an extended far-infrared shell around the AGB star R Cassiopeia and suggested that the interaction with the interstellar medium is responsible for shaping.…”
Section: Introductionmentioning
confidence: 99%
“…I mention here only an example of R Cas, which is one of the strong SiO maser sources (Cotton et al 2004). In the far infrared images between 60 and 160 microns, this star exhibts an extended far-IR emission of the size of about a few arcminutes (Ueta et al 2010). In their FIR images, the stellar position does not fall at the center of the emission, but slightly shifted to the East.…”
Section: Discussionmentioning
confidence: 88%
“…This occurs due to the motion of the star relative to interstellar medium. From a number of these observations, we can obtain the stellar motions in the interstellar medium (Ueta et al 2011). We can also obtain the proper motions of the central star from VLBI measurements.…”
Section: Discussionmentioning
confidence: 99%